An assessment-based model for exploring the solving of mathematical problems: Utilizing revised bloom's taxonomy and facets of metacognition. (December 2018) - Radmehr, Farzad; Drake, Michael
Highlights: Provide a method that can be used to review the assessment of mathematics. Examples are provided using RBT and Efklides's metacognition framework. Help to develop questions that target broader student thinking. A starting point for Faculties to reform their assessment of mathematics. Abstract: This paper provides a method that can be used to review the teaching, learning, and/or assessment of mathematics at either (or both of) the senior secondary and undergraduate levels. In this paper, how this method could be enacted is exemplified by considering the case of integral calculus. The method uses Revised Bloom's Taxonomy (RBT) (Anderson et al., 2001) in conjunction with Efklides's metacognition framework (Efklides, 2006, 2008) to design questions to address the different RBT cognitive processes and knowledge types. Using these two frameworks can help develop questions that target broader student thinking and a range of cognitive processes, including constructive ones, than traditional questions reach. In doing so, this method can be a starting point for Faculties seeking to reform their delivery and assessment of mathematics.